Discovery of Diverse Rodent and Bat Pestiviruses With Distinct Genomic and Phylogenetic Characteristics in Several Chinese Provinces - Wu, Zhiqiang; Liu, Bo; Du, Jiang; Zhang, Junpeng; Lu, Liang; Zhu, Guangjian; Han, Yelin; Su, Haoxiang; Yang, Li; Zhang, Shuyi; Liu, Qiyong; Jin, Qi (Frontiers in Microbiology, 2018)
Bats and rodents are widely distributed worldwide and can be native or intermediate reservoirs of many important zoonotic viruses. Pestiviruses are a group of virus species of the genus Pestivirus under the family Flaviviridae that can infect a wide variety of artiodactylous hosts, including swine and ruminants. Two classic types of pestiviruses; bovine viral diarrhea virus and classical swine fever virus, are important causative agents of mild-to-severe disease in bovine and swine hosts respectively and cause tremendous economic losses in these industries. Recent reports revealed that bats and rodents could also act as natural hosts of pestiviruses and an atypical porcine pestivirus, which cause serve disease in piglets, showed a close genetic relationship with a specific bat pestivirus, RaPestV-1. This study aimed to describe the detection and characterization of novel pestiviruses from bats and rodents in different locations by analyzing the available bat and rodent virome data from throughout China. Five bat pestiviruses and five rodent pestiviruses that are distinct from one another and from other known viruses were identified and sequenced. These viruses were identified from two bat species and four rodent species in different Chinese provinces. There were two distinct lineages present in these viruses, that differ from artiodactylous pestivirus. These findings expand our understanding of the genetic diversity of PestVs in bats and rodents and suggest the presence of a diverse set of pestiviruses in non- artiodactylous hosts. This study may provide new insight for the prevention of future viral disease outbreaks originating from bats and rodents.